THE EFFECT OF LAYER CHICKEN FARMING BUSINESS ON THE SOCIO-ECONOMIC IMPACT OF THE COMMUNITY - Nirnawati Dewi; Amruddin; Firmansyah; Rasdiana Mudatsir; Sahlan (Universitas Muhammadiyah Makassar, 2026)
This study aims to analyze the socioeconomic impacts and identify the challenges faced by layer chicken farms in Lassang Barat Village, Polongbangkeng Utara Subdistrict, Takalar Regency. The study employed purposive sampling to select research informants and utilized a qualitative descriptive method for data analysis. The research findings indicate that the presence of commercial layer chicken farms in Lassang Barat Village, Polongbangkeng Utara Subdistrict, Takalar Regency, has generated socioeconomic impacts. From a social perspective, these include the establishment of good relations between farmers and the community, the creation of social cooperation, the emergence of mutually beneficial social benefits, and the fostering of harmony and effective communication between farmers and the community. Meanwhile, from an economic perspective, the impacts include increased community income, the creation of jobs, the emergence of mutually beneficial economic benefits, and the improvement of the economy in Lassang Barat Village. The challenges faced by the layer chicken farming business in Lassang Barat Village, Polongbangkeng Utara Subdistrict, Takalar Regency, include, for farmers: unstable productivity, fluctuating selling prices, rising feed and medication costs, and seasonal chicken diseases. For the community, these include the smell from the chicken coops, disturbances to comfort, and the potential for social conflict.